2020
DOI: 10.1002/cbdv.202000369
|View full text |Cite
|
Sign up to set email alerts
|

Enriched Terpenes Fractions of the Latex of Euphorbia umbellata Promote Apoptosis in Leukemic Cells

Abstract: The current study was carried out by a bioguided fractionation of a hexane extract of the latex of Euphorbia umbellata against leukemic cells. Samples were analyzed by NMR, GC/MS, triterpenes quantification, and MTT reduction assay. Morphological, cell cycle, mitochondrial membrane potential and caspases 3/7 analyses were performed for the dichloromethane and ethanol fractions, and selectivity index for the dichloromethane fraction. NMR analysis presented characteristic signals of terpenes and steroids, data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Hence, our extract can be classified as selectively for MCF-7 breast cancer cell lines (SI ≥ 2). [ 18 ] These anticancer activities are corroborated with the morphological description contrast to experience morphological description, contrast cell deformation was observed in MCF-7-treated cells. The cells were observed to experience a shrinkage and lysis; indicating the inhibited cellular growth.…”
Section: Discussionsupporting
confidence: 58%
“…Hence, our extract can be classified as selectively for MCF-7 breast cancer cell lines (SI ≥ 2). [ 18 ] These anticancer activities are corroborated with the morphological description contrast to experience morphological description, contrast cell deformation was observed in MCF-7-treated cells. The cells were observed to experience a shrinkage and lysis; indicating the inhibited cellular growth.…”
Section: Discussionsupporting
confidence: 58%
“…In turn, recent studies show that the use of antioxidant compounds as part of the nutritional therapy of cancer patients has positive results in mitigating adverse effects generated by chemo and radiotherapy [58] . Another study also showed that fractions of terpenes enriched in E. umbellata latex promoted apoptosis in HL-60 leukemic cells, causing morphological changes compatible with the induction of apoptosis, altered cell cycle, depolarized cells, and the activation of caspase 3 and caspase 7 [59] . In general, caspase 3 mediates apoptosis by acting via the mitochondrial pathway [60] and terpenes activate caspase 3 activity as seen in tumor cells k-562, Hela, MCF-7 (breast cancer) and MDA-MB 231 (Breast cancer negative triple) [61] .…”
Section: Antitumor Potentialmentioning
confidence: 91%
“…The total of terpenes content was determined according presented by Cruz et al (2020). Each extract sample (10 mg) was resuspended individually in 1 mL of methanol; then, 100 μL of each solution was mixed with 150 μL of vanillin solution in glacial acetic acid (5 %, w/v) and 500 μL of perchloric acid solution.…”
Section: Terpenes Quantificationmentioning
confidence: 99%
“…Oliveira et al (2013) demonstrated that nonpolar compounds [as terpenes (euphol) and steroids (citrostadienol)] of E. umbellata latex promoted reduction in the volume of the tumor of melanoma in mice. Luz et al (2016) proved that nonpolar extracts of the same vegetal matrix have cytotoxic effects against different cancer cells lines and Cruz et al (2020) demonstrated that enriched terpene extracts of the latex promoted apoptosis in leukemic cells.…”
Section: Introductionmentioning
confidence: 99%